The Effect Of Implementing The Cooperative Learning Model STAD Type (Student Teams Achievement Division) On Students' Economic Learning Outcomes Class XI - Herlina Theresa Panjaitan; Lasma Siagian; Nova Yunita Sari Siahaan (STABN RADEN WIJAYA WONOGIRI, 2023)
This study aims to determine the effect of applying the cooperative learning model type STAD (Student Teams Achievement Division) on the economics learning outcomes of grade XI students at SMA Negeri 2 Lubuk Pakam. This research employed a quantitative approach with a quasi-experimental method using a One Group Pretest–Posttest design, involving a sample of 36 students selected through purposive sampling. The research instrument was a multiple-choice test that had been validated in terms of validity, reliability, difficulty level, and discriminating power. The findings indicate an improvement in students’ learning outcomes after the implementation of the STAD model, as evidenced by higher average posttest scores compared to pretest scores. The prerequisite tests showed that the data were normally distributed and homogeneous, making them suitable for further analysis. The simple linear regression analysis resulted in the equation Y = 27.069 + 2.114X with an R² value of 0.884, meaning that 88.4% of the variation in learning outcomes was influenced by the implementation of STAD. The t-test revealed t value = 16.118 > t table = 2.048 with a significance level of 0.000 < 0.05, thus confirming that the hypothesis was accepted. Moreover, the N-Gain score of 0.6819 (68.19%) fell into the medium-to-high category, indicating the effectiveness of the STAD model in improving students’ learning achievement. In conclusion, the application of the cooperative learning model type STAD has a positive and significant effect on economics learning outcomes and can serve as an innovative and effective instructional strategy in senior high schools, particularly at SMA Negeri 2 Lubuk Pakam